Iterating Infusion Clearer Views of Objects, Classes, and Systems - Anthony, Greg (Apress : Imprint: Apress, 2005)
Iterating Infusion: Clearer Views of Objects, Classes, and Systems is a one-of-a-kind book, not dependent on any single technology. Rather, it provides a way to integrate the most efficient techniques from a variety of programming methods, in a manner that makes designing and programming software look easy. Iterating Infusion presents comprehensive tools for you to best manage and work with object orientation. These include simplified fundamental concepts, popular language comparisons, advanced designing strategies, a broad usage progression, thorough design notations (interaction algebra), and data-oriented (fundamentally-OO) languages. The title, Iterating Infusion, alludes to the fact that any system has multiple, coexisting functional levels and that new levels-both lower and higher-are continually added to the same functional area. The practical effect is to bring processes into focus, always clarifying the vague. The extreme form of this is when separate but compatible technologies are brought together to create advancements; these can be baby-steps or great leaps, with varying amounts of effort. In more general terms, the same thing in a different context can take on much more power. And actually, this phenomenon is at the heart of object-oriented software. Readers have been confirming that, compared to books on just low-level details, Iterating Infusion presents cohesive insights that allow you to solve more problems with the same effort in more key places.